Canine blood oxygenation using ultra-low blood flow in an in vitro, single-circuit, extracorporeal membrane oxygenator model - Zeiler, Gareth Edward (University of Pretoria, 2024)
Dissertation (MMedVet (Anaesthesiology))--University of Pretoria, 2021.